CODE OF CONDUCT AS AN INSTITUTIONAL INSTRUMENT TO PRESERVE TRADITIONAL MARKETS - Leksono, Sonny; Anam, Choirul; Firdaus, Rizal Nur (Universitas Brawijaya, Indonesia, 2021)
This paper aims to establish a code of conduct framework in Pasar Besar Malang. The approach used is the qualitative grounded theory by involving market participants and market authorities as informants for ten months. Data analysis used is open coding, axial coding, and selective coding. Field findings stated that the code of conduct could make the arrangement more extensive than man’s cooperation in biographical, interactional, and organizations to increase the turnover for creating a sustainable traditional market. In addition, the code of conduct can create a rule, written or unwritten, at Pasar Besar Malang.